Controle Químico de Calacarus heveae Feres (Acari: Eriophyidae) em Seringueira - Vieira, Marineide; Gomes, Eduardo; Figueira, Janayna (BioAssay, 2009)
The rubber tree, Hevea brasiliensis (Willd. ex. Adr. de Juss.) Müell. Arg., can be attacked by several mite species. Among the phytophagous ones, Calacarus heveae Feres (Acari: Eriophyidae) can reach high population density levels on the upper surface of mature leaves and rubber trees can lose up to 75% of their leaves one or two months before the natural defoliation. The present work aimed to define a control strategy by evaluating the mite population development in areas treated with the acaricides azocyclotin, sulfur, cyhexatin, spirodiclofen and propargite,during the period from November, 2001 to June, 2002. Others sprays were performed when C. heveae population reached the threshold level of 0.5 mite/cm2 in each treatment. The acaricides were sprayed with the use of an air blast sprayer for rubber tree with a spray volume of 1.0 liter per plant. All tested products were efficient for C. heveae control, with immediate reduction in the mite population density levels. However, there was a great difference concerning the control period. Two applications of spirodiclofen and propargite were enough to keep the mite population below the level that can cause defoliation throughout the crop season, while four applications were necessary in the treatments with cyhexatin and sulfur. Among tested acaricides, spirodiclofen and propargite allowed higher leaf retention of rubber trees which were measured indirectly by the light intensity under the tree canopies.